2022
DOI: 10.7150/ijbs.70644
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbe-derived SCFA alleviates atrial fibrillation via GPR43/NLRP3 signaling

Abstract: Rationale: Dysbiotic gut microbiota (GM) and NLRP3 inflammasome are proarrhythmic factors in atrial fibrillation (AF). Herein, whether short-chain fatty acid (SCFA) produced from GM fermentation of dietary fiber serving as invisible mediators is yet unclear. Thus, the current study aimed to determine whether SCFA alleviated from NLRP3 signaling-mediated atrial remodeling protects AF development. Methods: First, a cross-sectional study based on the GC-MS metabolomics was performed to explore the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…| 7 of 10 Zuo et al, 2020Zuo et al, , 2022. Our major findings indicated that there is a significant association between dysbiosis in the gut microbiome with AF.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…| 7 of 10 Zuo et al, 2020Zuo et al, , 2022. Our major findings indicated that there is a significant association between dysbiosis in the gut microbiome with AF.…”
Section: Discussionmentioning
confidence: 71%
“…One human study demonstrated that increased TMAO synthesis can increase platelet hyperactivity, resulting in a high risk of AF after ablation procedures . Similarly, one other study found increased levels of TMAO after 12-18 months of AF catheter ablation (Zuo et al, 2022). However, the clinical data evaluating the correlation of TMAO with AF is inconclusive in many other studies (Papandreou et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Intestinal bacteria can produce SCFA, which is involved in the secretion of brain gut peptides by intestinal endocrine cells, such as glucagon like peptide 1, growth hormone releasing peptide (Ghrelin) and YY peptide. SCFA activates mammalian rapamycin target protein/signal transduction and transcriptional activator signal pathway through G-protein coupled receptor 43 and regulates the expression of brain gut peptide (Zuo et al, 2022). Brain gut peptide (such as Ghrelin) can participate in regulating hypothalamic regulatory nucleus and luteinizing hormone secretion.…”
Section: Brain-gut Axis and Pocsmentioning
confidence: 99%
“…Dietary fiber is a source of carbohydrates for the microbiota ( Coker et al., 2021 ; Zuo et al., 2022 ). The composition of the colonic microbiota is significantly influenced by diet and its assimilation in the small intestine ( Murga-Garrido et al., 2021 ).…”
Section: Diet-gut Microbiota-kidneymentioning
confidence: 99%